The experiences of cancer patients within the material hospital environment: Three ways that materiality is affective. (November 2020) - Wiltshire, Gareth; Pullen, Emma; Brown, Frankie F.; Osborn, Mike; Wexler, Sarah; Beresford, Mark; Tooley, Mark; Turner, James E.
Abstract: Improving the patient experience is widely recognised as an important goal in the delivery of high-quality healthcare. This study contributes to this goal with a particular focus on the role of the material hospital environment for patients being treated for cancer. Extending the burgeoning literature utilising materialist theoretical approaches in social science and medicine, we report on qualitative data with 18 participants who had received cancer treatment from one UK hospital. Our analysis offers a typology of ways in which the material hospital environment is affective: through patients' direct intra-actions with nonhuman materiality; through providing shared spaces within which human-human assemblages are actualised; and through being the material component of the practices of treatment. Within each process in this typology, the analysis highlights how the affective feeling states which play a critical role in patient wellbeing are in many ways contingent, fluid and context-sensitive. Amidst ambitions to improve the patient experience, these findings underline the significance of materialities of care and offer a broad explanatory typology with analytic and practical potential for healthcare staff, patient groups, architects and designers. Highlights: Cancer patients' experiences are contingent on the material environment of hospital settings. Materiality is affective through patients' direct intra-actions with nonhuman materiality. Materiality is affective through providing shared spaces within which human-human assemblages are actualised. Materiality is affective through being the material component in the practices of treatment.